Outcomes of HRSA-Funded Expansion of Physician Assistant Training Grants 2011–2016. Issue 3 (September 2021) - Rolls, Joanne; Lessard, Donovan; Smith, Tyler; Keahey, David
Abstract : Purpose: The Affordable Care Act (ACA), enacted in 2010, created the Expansion of Physician Assistant Training (EPAT) grant with the goal of increasing the number of physician assistants (PAs) entering primary care. There has been no analysis regarding the practice patterns of students graduating from EPAT-funded programs. This study aimed to describe the workforce impact of federal investment in PA education through the EPAT program. Methods: In 2018 the authors administered an anonymous electronic survey to all 27 EPAT PA programs funded from 2010 to 2015. The goal was to assess program and graduate characteristics, practice patterns, and intention to apply to similar future opportunities. The survey was IRB exempt. Results: There was a 59.30% response rate representing 366 total graduates, which reflected 62.46% of the 586 Health Resources and Services Administration (HRSA)-reported total EPAT-funded students. Of the respondents, 16.41% of EPAT recipients self-identified as non-White, 4.54% indicated Hispanic ethnicity, 53.65% identified as being of disadvantaged status, and 32.92% reported coming from rural backgrounds. Sixty-three percent entered primary care immediately following graduation, while 87.88% reported practicing primary care immediately after graduation or at the last point of contact. Fifty-two percent of EPAT graduates practiced in medically underserved areas (MUAs). Conclusion: Recipients of HRSA EPAT funding practiced in primary care specialties immediately following graduation at a rate that was 2.5 times higher than the national PA average. This specialty choice was durable for several years post-graduation. The EPAT program funded over 140 PA graduates who immediately practiced in MUAs. This funding supported a more racially and ethnically diverse student population and higher number of students coming from rural areas than the national average for PA students.